2003
DOI: 10.1074/jbc.m212935200
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase 9 Gene Encodes Multiple Protein Isoforms

Abstract: Histone deacetylases (HDACs) perform an important function in transcriptional regulation by modifying the core histones of the nucleosome. We have now fully characterized a new member of the Class II HDAC family, HDAC9. The enzyme contains a conserved deacetylase domain, represses reporter activity when recruited to a promoter, and utilizes histones H3 and H4 as substrates in vitro and in vivo. HDAC9 is expressed in a tissue-specific pattern that partially overlaps that of HDAC4. Within the human hematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 82 publications
2
145
1
Order By: Relevance
“…The adapter domain of class IIa HDACs contains specific residues that are subjected to various posttranslational modifications, such as proteolytic cleavage (Bakin and Jung, 2004;Liu et al, 2004;Paroni et al, 2004), ubiquitination , sumoylation (Kirsh et al, 2002;Petrie et al, 2003) and most importantly phosphorylation. In response to various stimuli, a set of serine residues in the adapter domain of class IIa HDACs is phosphorylated, creating docking sites for the 14-3-3 proteins (Grozinger and Schreiber, 2000;Wang et al, 2000).…”
Section: Structure Of Class Iia Hdacs: the N-terminal Adapter Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…The adapter domain of class IIa HDACs contains specific residues that are subjected to various posttranslational modifications, such as proteolytic cleavage (Bakin and Jung, 2004;Liu et al, 2004;Paroni et al, 2004), ubiquitination , sumoylation (Kirsh et al, 2002;Petrie et al, 2003) and most importantly phosphorylation. In response to various stimuli, a set of serine residues in the adapter domain of class IIa HDACs is phosphorylated, creating docking sites for the 14-3-3 proteins (Grozinger and Schreiber, 2000;Wang et al, 2000).…”
Section: Structure Of Class Iia Hdacs: the N-terminal Adapter Domainmentioning
confidence: 99%
“…HDAC4 and -9 are subject to sumoylation, at a lysine residue also conserved in HDAC5 (Tatham et al, 2001;Kirsh et al, 2002;Petrie et al, 2003). SUMO is believed to alter the interaction properties of its target, often affecting its localization within the cell (Seeler and Dejean, 2001).…”
Section: Other Posttranslational Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Hdac9 cDNAs have been cloned (AY032737, AY032738, and AY197371) and their predicted amino acid sequences share 92% identity with rat HDAC9FL. 15,19) Isoforms lacking the region encoded by exon 7 have also been identified in humans and found to be located in the cytoplasm. We showed that rat HDAC9∆7 too was selectively expressed in the cytoplasm, suggesting the function of the NLS encoded in exon 7 to be conserved in humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…15) When we started cloning Hdac9 cDNA, two predicted rat Hdac9 cDNA sequences (XM 576017 and XM 234063) were registered in the database, but they did not overlap. To isolate the full-length ORF, we performed 5 -RACE and RT-PCR.…”
Section: Cloning Of Rat Hdac9 Cdnamentioning
confidence: 99%